Answer:
Table F
Step-by-step explanation:
The equation is C = 0.75t. The variable c is for cost and t is for tickets. When we use substitution to solve the equation, we see that table F correctly represents the situation. In simpler terms, the equation is asking us to mutliply the cost PER ticket by the number of tickets.
0.75 * 1 = 0.75
0.75 * 2 = 1.50
0.75 * 3 = 2.25
0.75 * 4 = 3
And so on. As we can see, the only table that shows these values is in fact table F.
Hope this helps!
Answer:
Ok, we have a system of equations:
6*x + 3*y = 6*x*y
2*x + 4*y = 5*x*y
First, we want to isolate one of the variables,
As we have almost the same expression (x*y) in the right side of both equations, we can see the quotient between the two equations:
(6*x + 3*y)/(2*x + 4*y) = 6/5
now we isolate one off the variables:
6*x + 3*y = (6/5)*(2*x + 4*y) = (12/5)*x + (24/5)*y
x*(6 - 12/5) = y*(24/5 - 3)
x = y*(24/5 - 3)/(6 - 12/5) = 0.5*y
Now we can replace it in the first equation:
6*x + 3*y = 6*x*y
6*(0.5*y) + 3*y = 6*(0.5*y)*y
3*y + 3*y = 3*y^2
3*y^2 - 6*y = 0
Now we can find the solutions of that quadratic equation as:
![y = \frac{6 +- \sqrt{(-6)^2 - 4*3*0} }{2*3} = \frac{6 +- 6}{6}](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B6%20%2B-%20%5Csqrt%7B%28-6%29%5E2%20-%204%2A3%2A0%7D%20%7D%7B2%2A3%7D%20%3D%20%5Cfrac%7B6%20%2B-%206%7D%7B6%7D)
So we have two solutions
y = 0
y = 2.
Suppose that we select the solution y = 0
Then, using one of the equations we can find the value of x:
2*x + 4*0 = 5*x*0
2*x = 0
x = 0
(0, 0) is a solution
if we select the other solution, y = 2.
2*x + 4*2 = 5*x*2
2*x + 8 = 10*x
8 = (10 - 2)*x = 8x
x = 1.
(1, 2) is other solution
Ratios equivalent to 4:12 = 1:3
Answer:
True
Step-by-step explanation:
Answer:
y - 7 = -2(x - 4)
Step-by-step explanation:
We are asked to write the equation of a line in point slope form
Step 1 : find slope
We are given the slope to be -2
Slope m = -2
Step 2: substitute m into point slope form
y - y_1 = m( x - x_1)
y - y_1 = -2 ( x - x _1)
Step 3: substitute the point into the equation
y - y_1 = -2( x - x _1)
( 4 , 7)
x_1 = 4
y_1 = 7
y - 7 = -2( x - 4)
We don't need to open the bracket because we are asked to write the equation in a point slope form